Miejsce muzykoterapii w stymulowaniu rozwoju dzieci z niepełnosprawnością intelektualną - Jakoniuk-Diallo, Anna (Wydawnictwo Naukowe UAM, 2018)
Music therapy is a complex process conducive to the improvement of the functioning of the organism subjected to this type of action. It is a multifaceted action including various forms and methods of working with the use of music. In this text I present an analysis of the importance of such activities for the development of children with intellectual disabilities and try to assess the extent to which such activities are used in working with this group of people. The analysis of the ways of performing music therapy in relation to children with intellectual disabilities is illustrated by the results of a diagnostic survey.
The Role of Music Therapy in the Stimulation of Development of Children with Developmental Disability
Keywords: music therapy; disabled child; intellectual disability; rhythmic activities